Teoria econômica dos jogos e o ensino médio - Oliveira, Davi Lessa de (2017)
This work focuses on presenting the basic elements of the Economic Theory of Games in a way that is suitable for exposition at the mathematical level of high school education in Brazil. With that in mind, the work covers a brief historical context of the subject, classic games of Economic Theory of Games, what are pure and mixed strategies, methods of systematization, the concept of solution, methods to find solutions and, at the end, we suggest a Mathematical Workshop on Economic Theory of Games as a way to introduce the subject to high school students.